Resilience of Pesantren-Based Madrasahs in Yasinat, Jember: Adjusting to Educational Developments - Ridho, Akhsin; Damairi , Muhammad Uzaer (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study investigates the resilience of Pesantren-based Madrasahs in Yasinat, Jember, focusing on how they sustain their existence amid social, economic, and technological challenges. The research aims to explore the factors contributing to the durability of these institutions in maintaining educational quality and social relevance. A qualitative case study approach is employed, utilizing interviews, observations, and documentation as primary data collection methods. The findings reveal that these madrasahs exhibit notable resilience, primarily driven by integrating traditional values, active community engagement, and effective adaptations to technological advancements and educational curricula. This resilience ensures their ability to navigate and overcome challenges, preserving their societal role. In conclusion, despite external pressures, Pesantren-based madrasahs in Yasinat continue to thrive and maintain their educational mission, demonstrating significant capacity for adaptation and continuity.